If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(2x+3)+8=-6(7x+4)+3x
We simplify the equation to the form, which is simple to understand
7(2x+3)+8=-6(7x+4)+3x
Reorder the terms in parentheses
+(+14x+21)+8=-6*(7x+4)+3x
Remove unnecessary parentheses
+14x+21+8=-6+*(+7x+4+)+3x
Reorder the terms in parentheses
+14x+21+8=+(-42x-24)+3x
Remove unnecessary parentheses
+14x+21+8=-42x-24+3x
We move all terms containing x to the left and all other terms to the right.
+14x+42x-3x=-24-21-8
We simplify left and right side of the equation.
+53x=-53
We divide both sides of the equation by 53 to get x.
x=-1
| -2x+6x-3= | | (-4t+8)(4t+1)=0 | | -5X+6/5=9X+7/2 | | 3x-5y=19 | | 180-x=2x+12 | | 3(2x+3)=-2x+2 | | 7(x-12)-11=22x-275 | | 5(2x-5)-3(x+1)-18x= | | (n-4)(n+4)=n-4 | | 2x-5=55+7x | | -(3)/(y-5)=(-(8)/5y-25)+1 | | -6(x+4)+158=13+25 | | t(3t+27)=66 | | -4/6x=12/24 | | 4x+56=5432 | | 5+7x=-x+53 | | -(2x^2y+4z)+4z-7x^2y= | | 8-2w=2 | | -2/6x=6/12 | | 84=12(12y+3) | | 2x+3*x-1= | | 7x-43=52 | | 3X+3/5=-2X-7/4 | | 4x^2-20x+10=0 | | -14-(-12)=x/2 | | 7-3(5t-10)=-67 | | x+3=12-1x | | 49=3x+9 | | -5x-10=2x+11 | | 52=3x+7 | | 17x+30=4(3x+6)+5x+6 | | 7y+3(y-9)=6(y+1)-2 |